Poetyki i lektury momentalne. Między materią a metafizyką, czyli o paronomazji na przykładzie poezji kobiet - Grądziel-Wójcik, Joanna (Poznańskie Studia Polonistyczne. Seria Literacka, 2017)
The paper investigates manners of linguistic description of psychosomatic, autobiographically interpreted experience in contemporary women’s poetry, which is analyzed in the context of the poetics of the moment, with reference to Hans Ulrich Gumbrecht’s concept of “poetry as a mode of attention.” The authoress is particularly interested in the figure of paronomasia, evoking homonymic, parallel spheres: the material and the transcendental one. The article contains close reading interpretations of poems by, among others, Krystyna Miłobędzka, Teresa Ferenc, Bogusława Latawiec and Ludmiła Marjańska, in which paronomasia introduces the reader into a dual dimension of existence, both anchoring the subject in the physical, bodily reality and provoking metaphysical questions.